In the Spotlight: How International Attention Affects Militant Behavior - Breslawski, Jori (Terrorism and political violence, 2021)
Why do some militant groups use rhetoric that indicates intentions of democratic governance, while others are silent on these issues, or even clearly oppose them? In this article, I explore militant groups’ desire for external legitimacy, and seek to explain when they are willing to make costly promises to follow liberal norms. I argue that human rights media attention has a significant effect on group behavior. Specifically, militant groups are more likely to use democratic rhetoric when they are “in the spotlight,” which results in a higher likelihood of external legitimacy in exchange for following costly liberal norms. Using the Minorities at Risk Organizational Behavior (MAROB) data for the Middle East, Eastern Europe, and Russia, as well as a historical analysis of three militant groups in Indonesia, I find that militant groups residing in areas that receive a large amount of media attention are more likely to support democratic practices.